An improvement of an RFID indoor positioning system using one base station - Hatthasin, Upady; Thainimit, Somying; Vibhatavanij, Kemathat; Premasathian, Nol; Worasawate, Denchai (My University, 2009)
The proliferation of mobile computing devices and wireless positioning networks has fostered a growing interest in location-aware systems and devices. Most technologies such as Radio Frequency IDentification (RFID), RADAR, etc, use at least three Base Station (BS) for calculating position of target objects. This paper describes an improvement of the previous OneBS algorithm [13]. The proposed system uses only one BS based on the RFID infrastructure for positioning target tags amid the clutter of indoor interference environments. We proposed to fuse the Round-trip Time of Flight (RTOF) and the Received Signal Strength (RSS) in the positioning algorithm. Both information are kept in an intersection Box (iBox). The RTOF information is used to focus a target tag's position among groups of four-nearestneighbor reference tags kept within iBox. Then, the RSS information is weighted using the weighted center of gravity technique to estimate a location of the target tags. Our experiments are based on Three Dimension (3D) materials within interference environments. The interference environments are simulated based on Uniform Geometrical Theory of Diffraction (UTD), for measuring signals in each specific area. Our proposed algorithm gains 50 percents better average distance error compared to the OneBS algorithm.
Keywords: Indoor positioning system; Locating system; One base station approach; RFID; RSS-RTOF; RTOF- RSS; UTD